Socio-Economic Assessment of the Relationship between Value Added Tax and Economic Sectors in the RA - Panosyan, Meri; Sahakyan, Gnel (Bulletin of Yerevan University G: Economics, 2024)
The article assesses the impact of the value-added tax (VAT) on the sectors of the RA economy, comparing the growth rates of these sectors with the analysis of the VAT growth rate. RA industry, construction, trade, and services were considered as areas of study. To address the problem presented in the article, socio-economic relations between the considered sectors and VAT were studied. Regression analysis of the identified relations was conducted using quantitative analysis methods, and the degree of dependence of the sectors of the Republic’s economy on value-added tax was evaluated. The research was conducted using the Eviews 10 statistical computer program, where multifactor regression models were constructed, and their parameters were estimated using the method of least squares. The results of the performed regression analysis indicated a significant dependence between the examined sectors and VAT. Taking into account the results of the model evaluation, it was concluded that, under otherwise equal conditions, construction volumes increased by 0.8 % with a 1 % rise in the VAT growth rate. Simultaneously, the trade turnover growth rate increased by 0.6 % with a corresponding 1 % increase in the VAT growth rate. Additionally, the rate of growth of the volume of services (excluding trade) rose by 0.4 %, and the rate of growth of the volume of industrial output increased by 0.3 % with a corresponding 1 % increase in the VAT growth rate.